Deleuze and the political - Patton, Paul (Thinking the political., 2000)
With clarity, precision and economy, Paul Patton synthesizes the full range of Deleuze's work. He interweaves with great dexterity motifs that extend from his early works, such as Nietzsche and Philosophy, to the more recent What is Philosophy? and his key works such as Anti-Oedipus and Difference and Repetition. Throughout, Deleuze and the Political demonstrates Deleuze's relevance to theoretical and practical concerns in a number of disciplines including philosophy, political theory, sociology, history, and cultural studies.